POST TRANSFUSION HEPATITIS C TRANSMISSION FROM SCREENED BLOOD: Post Transfusion hepatitis C Transmission - Raza, Shahid; Abrar, Shaukat; Tanveer, Amjad; Khan, Badshah (Pakistan Armed Forces Medical Journal, 2008)
.